Endometriosis and Risk of Coronary Heart Disease. (May 2016) - Mu, Fan; Rich-Edwards, Janet; Rimm, Eric B.; Spiegelman, Donna; Missmer, Stacey A.
Abstract : Background—: Endometriosis is a prevalent gynecologic disease associated with systemic chronic inflammation, heightened oxidative stress, and atherogenic lipid profile that may increase women's risk for coronary heart disease (CHD). Methods and Results—: We examined the prospective association between laparoscopically confirmed endometriosis and subsequent CHD among 116 430 women in the Nurses' Health Study II (1989–2009). Participants with a history of heart disease and stroke were excluded. When compared with women without endometriosis, women with laparoscopically confirmed endometriosis had a higher risk of myocardial infarction (relative risk, 1.52; 95% confidence interval, 1.17–1.98), angiographically confirmed angina (1.91; 1.59–2.29), coronary artery bypass graft surgery/coronary angioplasty procedure/stent (1.35; 1.08–1.69), or any of these CHD end points combined (1.62; 1.39–1.89), independent of potential demographic, anthropometric, family history, reproductive, and lifestyle confounders. Relative risk for the combined CHD end point was highest among women aged ⩽40 years (3.08; 2.02–4.70) and decreased as age increased (40< age ⩽50 years, 1.65; 1.35–2.02; 50< age ⩽55 years, 1.44; 1.07–1.94; and age >55 years, 0.98; 0.56–1.72; P value, test for heterogeneity=0.001). Having had a hysterectomy/oophorectomy was associated with higher risk of combined CHD compared with not having had a hysterectomy/oophorectomy (1.51; 1.34–1.71). A percentage of 42 of the association between endometriosis and CHD could be explained by greater frequency of hysterectomy/oophorectomy and earlier age at surgery after endometriosis diagnosis. Conclusions—: In this large, prospective cohort, laparoscopically confirmed endometriosis was associated with increased risk of CHD. The association was strongest among young women. Hysterectomy/oophorectomy was associated with higher risk of CHD and could partially explain the association between endometriosis and CHD.